2019
DOI: 10.1093/bmb/ldz014
|View full text |Cite
|
Sign up to set email alerts
|

Global nurse shortages—the facts, the impact and action for change

Abstract: This is a pre-copyedited, author-produced version of an article accepted for publication in British Medical Bulletin following peer review. The version of record Drennan, Vari M and Ross, Fiona (2019) Global nurse shortages : the facts, the impact and action for change. British Medical Bulletin, 130(1), pp. 25-37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
264
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(311 citation statements)
references
References 24 publications
4
264
0
Order By: Relevance
“…In this study, organisational commitment was identified to have the greatest impact on nurses’ intent to leave. This result is consistent with that of previous studies (Drennan & Ross, ; Moon & Han, ; Nantsupawat et al, ), confirming that organisational commitment has the greatest impact on nurses’ intent to leave. The mean organisational commitment score of our participants was 2.80 out of 5, which is lower than that among Korean hospital nurses measured with the same tool in previous studies: 3.02 (Park, ) and 2.90 (Jin & Kim, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, organisational commitment was identified to have the greatest impact on nurses’ intent to leave. This result is consistent with that of previous studies (Drennan & Ross, ; Moon & Han, ; Nantsupawat et al, ), confirming that organisational commitment has the greatest impact on nurses’ intent to leave. The mean organisational commitment score of our participants was 2.80 out of 5, which is lower than that among Korean hospital nurses measured with the same tool in previous studies: 3.02 (Park, ) and 2.90 (Jin & Kim, ).…”
Section: Discussionsupporting
confidence: 92%
“…High turnover and the consequent shortage of nurses is one of the most serious problems affecting the field of health care worldwide, impacting an array of domains, from the quality of nursing service to organisational productivity (Drennan & Ross, ). In 2017, the rate of Korean nurses’ turnover was reported to be 13.8% (Hospital Nurses Association, ), more than twice the appropriate turnover rate of 5%–7% proposed by Toffler ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group authorship Not applicable. 1 Faculty of Nursing, Edmonton Clinic Health Academy, University of Alberta, Edmonton, AB T6G 1C9, Canada. 2 Faculty of Education, University of Alberta, Edmonton, AB T6G 2G5, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Nursing shortages around the world have led to unprecedented rates of international and interregional nurse migration [1]. Recent findings revealed that 40% of nursing positions in the Caribbean remain vacant, primarily due to nurse migration [2].…”
Section: Introductionmentioning
confidence: 99%